2019
DOI: 10.3389/fpsyg.2019.00262
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Experiential Avoidance and Parental Control in the Association Between Parent and Child Anxiety

Abstract: Parenting behavior and practices contribute to the intergenerational relationship between parent and child anxiety, with parental control being a consistent predictor of child anxiety. Parental experiential avoidance refers to how a parent copes with their internal world in the context of parenting. Little is known about how this relatively new parenting concept relates to child anxiety. The current study tested the indirect effect of parent anxiety on child anxiety through parental control and parental experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…So, it can simply be concluded that the actions and reactions of the children are influenced by the style of problem-solving strategies adopted by their parents. But a large number of researchers concluded that anxiety is directed by environmental forces (Chow et al, 2018;Emerson et al, 2019;Ren et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…So, it can simply be concluded that the actions and reactions of the children are influenced by the style of problem-solving strategies adopted by their parents. But a large number of researchers concluded that anxiety is directed by environmental forces (Chow et al, 2018;Emerson et al, 2019;Ren et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…FA may provide parents with a means of actively avoiding their own anxiety or discomfort in having to face their child's anxiety. Parental experiential avoidance has been cited as a relevant factor and a significant predictor of child anxiety, after controlling for parent anxiety and control (Emerson et al, 2019). Meyer et al (2018) reported that parental use of FA may be related to parental beliefs that not providing FA would result in the child losing behavioural and emotional control.…”
Section: Willingnessmentioning
confidence: 99%
“…Parental psychological flexibility is defined as the ability to be fully aware of the emotions and thoughts related to childcare, taking them in perspective, and redirecting behavior into parenting practices in line with values [ 8 ]. In contrast, experiential avoidance refers to attempts to reduce or eliminate events or stimuli that produce discomfort [ 9 ]. Experiential avoidance responses have been associated with problems of anxiety [ 9 ], stress [ 10 ], depression and family conflict [ 11 ] in both children and parents.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, experiential avoidance refers to attempts to reduce or eliminate events or stimuli that produce discomfort [ 9 ]. Experiential avoidance responses have been associated with problems of anxiety [ 9 ], stress [ 10 ], depression and family conflict [ 11 ] in both children and parents. Psychological inflexibility in parenting practices can lead to dysfunctional reactions or interactions as a result of cognitive fusion and avoidance of the emotional distress associated with parenting, i.e., avoiding children’s reactions, overprotective or impulsive parental reactions that occur with the function of trying to avoid confronting situations or private events (thoughts, emotions, feelings, sensations, etc.)…”
Section: Introductionmentioning
confidence: 99%